2015
DOI: 10.1111/mpp.12292
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of BcStr2 in methionine biosynthesis, vegetative differentiation, multiple stress tolerance and virulence in Botrytis cinerea

Abstract: The Str2 gene encodes a cystathionine γ-synthase that is a key enzyme in methionine (Met) biosynthesis in Saccharomyces cerevisiae. Met plays a critical role in protein synthesis and diverse cellular processes in both eukaryotes and prokaryotes. In this study, we characterized the Str2 orthologue gene BcStr2 in Botrytis cinerea. The BcStr2 mutant was unable to grow on minimal medium (MM). In addition, conidia of the mutant were unable to germinate in water-agar medium within 15 h of incubation. Supplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
(64 reference statements)
1
10
2
Order By: Relevance
“…LGI2-1, found exclusively in this clonal complex and also harboring a putative cystathionine ␥-synthase gene. The extent to which this gene mediates unique stress-related adaptations in these strains, such as those shown with cystathionine ␥-synthase of the fungal agent Botrytis cinerea in relation to resistance to osmotic, oxidative, and thermal stresses (21), remains to be determined. WGS-based analysis of LGI2 revealed sequence divergence in two other strains, J3422 (serotype 4b; CC1) and 2008-911 (serotype 1/2c; CC9) ( Fig.…”
Section: Listeria Arsenic Resistance Genomic Islandmentioning
confidence: 99%
“…LGI2-1, found exclusively in this clonal complex and also harboring a putative cystathionine ␥-synthase gene. The extent to which this gene mediates unique stress-related adaptations in these strains, such as those shown with cystathionine ␥-synthase of the fungal agent Botrytis cinerea in relation to resistance to osmotic, oxidative, and thermal stresses (21), remains to be determined. WGS-based analysis of LGI2 revealed sequence divergence in two other strains, J3422 (serotype 4b; CC1) and 2008-911 (serotype 1/2c; CC9) ( Fig.…”
Section: Listeria Arsenic Resistance Genomic Islandmentioning
confidence: 99%
“…In F. graminearum, fungal mutants lacking FgMetB exhibited decreased virulence to wheat, which is consistent with low levels of deoxynivalenol (DON) production in wheat kernels (20). In Botrytis cinerea, mutants lacking BcMetB exhibited significantly decreased virulence on host plant tissues (30). The ability to detoxify host-generated ROS is critical to the pathogenicity in numerous plant pathogens.…”
Section: Inactivation Of Aametr Affects Several Critical Genes Relatementioning
confidence: 75%
“…In F. graminearum , fungal mutants lacking FgMetB exhibited decreased virulence to wheat, which is consistent with low levels of deoxynivalenol (DON) production in wheat kernels ( 20 ). In Botrytis cinerea , mutants lacking BcMetB exhibited significantly decreased virulence on host plant tissues ( 30 ). Consistent with our previous findings, this study demonstrated the important role of AaMetB , AaMetC , and AaMetX in the full pathogenicity of A. alternata , indicating that AaMetB , AaMetC , and AaMetX , involved in methionine biosynthesis, are critical factors related to the virulence of fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers for the construction of gene deletion plasmids and other primers used in this study are presented in Table S2. Fungal protoplast preparation and transformations were performed as previously described with some modifications (Shao et al ., 2016). More details of the construction of the gene deletion mutants and complement strains are shown in Methods S1.…”
Section: Methodsmentioning
confidence: 99%